Floristic composition of the tree stratum of a semideciduous mesophytic forest in the municipality of Botucatu, São Paulo state - Gabriel, JLC; Pagano, S. N. (Inst Tecnologia Parana, 1993)
The floristic composition was studied in an area of semideciduous mesophytic forest, with 120 ha, in the municipality of Botucatu, SP, Brazil. This forest lies on the ascent of the Cuesta of Botucatu. Due to the heterogeneity of the relief, for the sampling process, the forest was divided in three regions: the upper one (comprising the strip of forest on the plateau), middle on (the forestal area lied on the ascent properly said) and the lower one (the strip of forest on the plain). The tree sampling regions showed some differences among them and this must be connected to the differences in the soil.
Keywords: FLORISTIC; SEMIDECIDUOUS MESOPHYTIC FOREST; TREE